Antibiotic legacies shape the temperature response of soil microbial communities - Wepking, Carl; Lucas, Jane M.; Boulos, Virginia S.; Strickland, Michael S. (Frontiers in Microbiology, 2024)
Soil microbial communities are vulnerable to anthropogenic disturbances such as climate change and land management decisions, thus altering microbially-mediated ecosystem functions. Increasingly, multiple stressors are considered in investigations of ecological response to disturbances. Typically, these investigations involve concurrent stressors. Less studied is how historical stressors shape the response of microbial communities to contemporary stressors. Here we investigate how historical exposure to antibiotics drives soil microbial response to subsequent temperature change. Specifically, grassland plots were treated with 32-months of manure additions from cows either administered an antibiotic or control manure from cows not treated with an antibiotic. In-situ antibiotic exposure initially increased soil respiration however this effect diminished over time. Following the 32-month field portion, a subsequent incubation experiment showed that historical antibiotic exposure caused an acclimation-like response to increasing temperature (i.e., lower microbial biomass at higher temperatures; lower respiration and mass-specific respiration at intermediate temperatures). This response was likely driven by a differential response in the microbial community of antibiotic exposed soils, or due to indirect interactions between manure and soil microbial communities, or a combination of these factors. Microbial communities exposed to antibiotics tended to be dominated by slower-growing, oligotrophic taxa at higher temperatures. Therefore, historical exposure to one stressor is likely to influence the microbial community to subsequent stressors. To predict the response of soils to future stress, particularly increasing soil temperatures, historical context is necessary.